PERBEDAAN PERSEPSI MAHASISWA AKUNTANSI MENGENAI LEARNING MANAGEMENT SYSTEMS (LMS) (Studi Empiris Pada Mahasiswa S1 Akuntansi Universitas Diponegoro dan Universitas Semarang) - Amita Suryaningsih; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
This  study  aims  to  analyze  the  accounting  students  perception  of  a  Learning Management System (LMS). This study examined differences of perception between accounting students from public universities with accounting students from private universities of a Learning Management System (LMS). In addition, this study also examine the factors that influence the accounting students perception about usefulness of Learning Management System (LMS). These factors are the lecture notes usefulness, student engagement  with  module,  discussion  forum,  and  Other  Virtual  Learning  Environment (VLE) tools (Basioudis, et al; 2012).This study used primary data and secondary data. The primary data obtained through distribution of questionnaires to accounting students at the Diponegoro University (UNDIP) and the Semarang University (USM). One hundred and thirty questionnaires was distributed, and 123 questionnaires was collected properly. The data is analyzed using independent sample t-test and regression analysis.The result of this research show that accounting students perception from public universities and private universities of a Learning Management System (LMS) is similar. In addition 75.7% of accounting student perceptions about usefulness of learning Management System (LMS) explained by factors in the model. Using significance 0.10, t test results showed that the factors in the model have positive influence on accounting students perception about usefulness of Learning Management System (LMS).